1970
DOI: 10.1001/archpedi.1970.02100050418006
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Unexpected Death in Infancy Syndrome

Abstract: Sudden unexpected death (SUD) occurs annually in the United States in more than 15,000 infants less than 6 months old\p=m-\the greatest mortality during the first year after the neonatal period. These deaths are not only unexpected but mostly unexplained, and most of the hypotheses proposed for causation have been disproved. A previous communication reported 28 instances among 18,000 infants who were under regular supervision; additional cases may simply not have been retrieved. Almost all of these were diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…There is a widely held conviction that small infants are unable to breathe through their mouths (Beinfield, 1954;Moss, 1965;Ingall et al, 1965;Pracy, 1972), and it has been suggested that nasal obstruction might be a causative factor in sudden unexpected death in infancy (SUDI) (Emery, 1958;Beinfield, 1959;Shaw, 1968. A small number of infants have been described (Anderson and Rosenblith, 1971) who died unexpectedly in the first year and who recorded slow inadequate neonatal responses to stimuli applied to the nose and mouth during the Modified Graham Behaviour Test (Rosenblith, 1961).…”
mentioning
confidence: 99%
“…There is a widely held conviction that small infants are unable to breathe through their mouths (Beinfield, 1954;Moss, 1965;Ingall et al, 1965;Pracy, 1972), and it has been suggested that nasal obstruction might be a causative factor in sudden unexpected death in infancy (SUDI) (Emery, 1958;Beinfield, 1959;Shaw, 1968. A small number of infants have been described (Anderson and Rosenblith, 1971) who died unexpectedly in the first year and who recorded slow inadequate neonatal responses to stimuli applied to the nose and mouth during the Modified Graham Behaviour Test (Rosenblith, 1961).…”
mentioning
confidence: 99%
“…The 'final common pathway' of death (assumed to be identical in most cases) is, however, unknown. The consensus view is that throughout life these infants are essentially healthy; they die because while passing through a developmental stage of physiological vulnerability some critical combination of extrinsic and intrinsic factors occurs which proves lethal through either (a) a respiratory mechanism-in whose production various processes have been incriminated (e.g., Bergman et al, 1970;Ray, Beckwith, Hebestreit, and Bergman, 1970;Shaw, 1970); (b) a lethal cardiac arrhythmia or conduction disturbance-for which an anatomic basis has been demonstrated (James, 1968); or (c) a hypersensitivity reaction to antigens at present unidentified but often thought to be cow's milk proteins (e.g., Parish et al, 1960b;Gunther, 1966). Numerous other hypotheses have been postulated but they are either untenable or purely speculative.…”
mentioning
confidence: 99%
“…Asphyxial death in congenital choanal atresia can be the price of this inability to mouth breathe. In choanal stenosis where respiratory work is greatly increased, or in normal babies it is very unusual to see mouth breathing, and nasal obstruction has been suggested as a cause of sudden, unexpected death in infancy (Shaw, 1970).…”
mentioning
confidence: 99%